Preliminary Physicochemical Contents and Antioxidant Properties of Coconut Water in Trinidad and Tobago - Ismaila, Sani (Polish Journal of Natural Sciences, 2025)
Abstract The chemical, mineral, and antioxidant content of two different species(yellow & green) of young coconut water in Trinidad and Tobago was quantified and compared coconuts The Total phenolic content (TPC),2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, Total soluble solids (TSS), Titratable acidity (TA), pH, turbidity, and mineral assay were tested Data obtained showed tentative concentrations of minerals, chemical properties, and antioxidant activity. The green (Atlantic tall) coconut water showed higher antioxidant activity with the DPPH and TPC assays compared to the yellow (Malayan dwarf) coconut water (p< 0.05). The yield of the crude extract was slightly higher in the yellow coconut water (p>0.05). No significant difference was observed in Total soluble solids (TSS) and pH between the two-coconut water (p>0.05). The titratable acidity of the green coconut water was higher (p<0.05). The yellow coconut water was more turbid (p<0.05). The yellow coconut water was higher in Na, K, Ca, and Mg (p< 0.05) but showed no significance in Fe between the two (p>0.05). This indicates that coconut water from Trinidad and Tobago contains high minerals and antioxidants.